2022
DOI: 10.33711/yyuefd.1067613
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of The General Trends in The Studies Conducted on Self-Regulation in Turkey

Abstract: Bu araştırmanın amacı Türkiye’de öz düzenleme ile ilgili yapılan araştırmaların incelenmesi ve bu alanda nasıl bir eğilim olduğunun ortaya konulmasıdır. Araştırma kapsamında 2000-2020 yılları arasında gerçekleştirilen ve amaçlı örnekleme yöntemi ile seçilen 295 araştırma analiz edilmiştir. Araştırma sonucunda öz düzenlemeye yönelik araştırmaların 2010 yılı ve sonrasında büyük bir artış gösterdiği, örneklem büyüklüğü açısından en fazla 101-300 örneklem grubuyla, en fazla üniversite öğrencileriyle, en az ilkokul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Similar to the findings of this study, Eskici & Çayak (2017) examined the master's theses conducted in the department of educational sciences and found that most of the data were obtained from teachers. Tutkun et al (2022) examined the research on self-regulation in Turkey and found that university students were mostly preferred as the sample group.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the findings of this study, Eskici & Çayak (2017) examined the master's theses conducted in the department of educational sciences and found that most of the data were obtained from teachers. Tutkun et al (2022) examined the research on self-regulation in Turkey and found that university students were mostly preferred as the sample group.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…While developing the evaluation form, the purpose of the study and the classifications in similar studies (Can Yaşar & Aral, 2011;Çopur & Tezel Şahin, 2022;Gülay Ogelman & Güngör, 2022;Tutkun et al, 2022) were taken into consideration. The evaluation form includes sections on the name of the thesis, thesis number, author name, type of thesis, year of completion, university, institute, research design, sample group, measurement tools and research results.…”
Section: Data Collection Toolmentioning
confidence: 99%